PENGARUH PERUBAHAN SUKU BUNGA TERHADAP PERHITUNGAN PREMI NETO TAHUNAN ASURANSI KESEHATAN INDIVIDU - PRADIPTA, YOGI; WIDANA, I NYOMAN; SUGIARTO, YOHANES BAMBANG (E-Jurnal Matematika, 2013)
Health insurance is a type of insurance product that specifically guarantees for health care or treatment. Individual and collective health insurance are the two categories of health insurance. Estimated premiums are determined according to death rate, sex, age, level of interest and administration costs. The interest rate relied on may vary between insurers. This study used three different interest rates for the calculation of annual net premium on individual health insurance based on RP-2000 Male & Female Combined Healthy Table and the Indonesian Mortality Table (TMI) 1999. The results indicated that an increase in interest rate causes a decrease in the premium, and vice versa. This study concludes that changes in interest rate affect the calculation of annual net premium on individual health insurance which are either renewed or not renewed.
Keywords: individual health insurance; the interest rate forecast; net premium